Cisco Networking Academy Program: it essentials II, Network operating companion guide (Cisco Systems, 2003)
Cisco Networking Academy Program IT Essentials II: Network Operating Systems Companion Guide is the Cisco approved textbook that supports the Hewlett-Packard sponsored web-based course of the Cisco Networking Academy Program. This book and its companion titles from Cisco Press prepare students for the CompTIA Server+ certification exam and, when studied in conjunction with the Fundamentals of UNIX course and its related titles, the CompTIA Linux+ certification exam. It introduces readers to basic networking concepts, NOS management and administration, and network security. It also includes an overview of Windows NT/2000, Windows XP, Linux, and Novell NetWare. This book prepares readers to become server systems specialists who can perform basic installation, operation, administration, and troubleshooting services. Cisco Press is a collaboration between Cisco Systems, Inc., and Pearson Education that is charged with developing high-quality, cutting-edge educational and reference products for the networking industry. The products in the Cisco Networking Academy Program series are designed to prepare students for careers in the exciting networking field. These products have proven to be strong supplements to the web-based curriculum and are the only print companions that have been reviewed and endorsed by Cisco Systems for Cisco Networking Academy Program use.